2020
DOI: 10.1177/1362361320964306
|View full text |Cite
|
Sign up to set email alerts
|

Emotional self-awareness in autism: A meta-analysis of group differences and developmental effects

Abstract: Emotional self-awareness is increasingly suggested to be an area of difficulty in autism that may predict socioemotional outcomes for this population. However, whether emotional self-awareness is consistently diminished in autism across age and methodology remains unclear. We systematically reviewed 47 papers measuring emotional self-awareness in autistic ( n = 1387) and non-autistic ( n = 1433) participants. Most studies relied on self-report. Of studies testing for group differences, the majority (32/41) fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 92 publications
1
22
0
1
Order By: Relevance
“…Although a recent meta‐analysis (Huggins, Donnan, et al, 2021) clearly demonstrated poorer emotional self‐awareness in autistic individuals, and especially in adults, Huggins et al note the heavy reliance on self‐report measures such as the Toronto Alexithymia Scale (Bagby et al, 1994). They suggest that such self‐reports may simply reflect autistic individuals' underestimation of their own competencies in this domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent meta‐analysis (Huggins, Donnan, et al, 2021) clearly demonstrated poorer emotional self‐awareness in autistic individuals, and especially in adults, Huggins et al note the heavy reliance on self‐report measures such as the Toronto Alexithymia Scale (Bagby et al, 1994). They suggest that such self‐reports may simply reflect autistic individuals' underestimation of their own competencies in this domain.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have reported similar challenges when examining self-reported measures of pain in autistic children with intellectual disability (Fitzpatrick et al, 2020 ). Furthermore, meta-analyses of self-report measures have shown that emotional self-awareness is diminished in autism (Huggins et al, 2021 ). This barrier could be explained by alexithymia, which is a common trait in autism characterized by difficulties in identifying and describing one’s own emotions (Griffin et al, 2016 ; Kinnaird et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emotional self-awareness, generally assessed by self-reported alexithymia measures, did not differ between children with and without ASD before the age of 12. However, individuals with ASD become less aware of their own emotions from adolescence into adulthood, while TD adolescents and adults do not exhibit age-related changes (see Figure 6 in Huggins et al, 2021 ). This decrease in emotional self-awareness is likely to undermine emotion regulation, an important skill, by adulthood in those with ASD ( Reyes et al, 2019 ).…”
Section: Literature Assessing Longitudinal and Age-related Changementioning
confidence: 99%